Pengembangan Media Pembelajaran Website Materi Unsur, Senyawa, dan Campuran dalam Kue Jojorong Banten untuk Memfasilitasi Kecakapan Literasi Digital Peserta Didik SMP - Lisnurhaeni; Lukman Nulhakim; Trian Pamungkas Alamsyah (PendIPA Journal of Science Education, 2026)
Digital literacy skills are one of the importantant competencies that students need too have to keep up with technological developments and support learning in the digital era. However, based on observations, the digital literacy skills of middle school students are consideres low. The use of learning media is not yet optimal, lacks interactivity, and has not taken full advantage of digital technology potential in science learning. One solution is by providing digital learning media that can present material in an interactive, contextual, and relevant way to the students’environment. This study aims to describe the ectent of validity and student responses to alearning website on the material of elements, compounds, and maxtures in Jojorong Banten cake to facilitate digital literacy skills for junior high school students. The method used is Research and Developments (R&D) wit the ADDIE model, limited up to the implementation stage. The instruments used were validation sheets and student response questionnaires. The product validity level was measured using validation sheets validated by three content expert lecturers, three media expert lecturers, and three junior high school science teachers, after the instruments had previously been validated by an instrument expert (judgment). The validation results showed that the content expert got 94.87%, the media expert 89.23% and the junior high school science teacher 90.19%, all rated as “Very Valid”. After ome revisions, a limited trial was done to see the students’responses, which scored 87.14%, rated as a “Very Good”. This shows that the learning website designed to support digital literacy skills meets the validity criteria and got positive feedback from students as a learning tool thah helps junior high school students improve their digital literacy skills.